Clinical outcomes after total excision of transobturator tape inserted for treatment of stress urinary incontinence. Issue 4 (24th February 2023) - Abbas, Nazish; Virdee, Tonicka; Basu, Maya; Iles, David; Kanitkar, Surya; Kearney, Rohna; Khan, Hamayun; Ward, Karen; Reid, Fiona
Abstract: Introduction: Midurethral tapes (MUTs) were the most common surgical treatment for stress urinary incontinence (SUI) between 2008 and 2017. Transobturator tapes were introduced as a novel way to insert MUTs. Some women have experienced life‐changing complications, and opt to undergo a total excision of transobturator tape (TETOT). There is a paucity in evidence about the outcomes of TETOT, which is a complex operation. This study aims to report clinical outcomes of all women who underwent TETOT in a specialist mesh center. Methods: All women between 2017 and 2022 who underwent TETOT in one mesh center were reviewed. Background demographics and preoperative symptoms were recorded retrospectively. Outcome data were collected using patient global impression of improvement (PGI‐I) scales via telephone review and analyzed using SPSS 25. Results: Forty‐five women underwent telephone review in May 2022, on average 27.9 months (range: 3−60) after TETOT. Mean age was 55 and body mass index (BMI): 30; 82% were postmenopausal, 20% were smokers, and 73.3% had recurrent SUI before excision. Indications for excision were infection (4%), vaginal exposure (24%), urethral perforation (9%), and chronic pain not associated with other complications (60%). Two women with recurrent SUI opted for a concomitant fascial sling; both reported a PGI of "very much improved" regarding SUI postoperatively. Only 12 women (26.5%) did not have SUI before excision; of these 9 (75%) reported new SUI postoperatively. Pain improved for 57.8%, but worsened for 24.4%. Although not statistically significant ( p = 0.055), more women who underwent TETOT for pain alone reported worsening pain than those with pain with an additional complication (37% vs. 5.55%). Overall, 62.2% women felt "better" after their excision, 17.8% felt "worse." Discussion: After TETOT, 62% of women felt better. Improvement in pain was reported by 58%—those with chronic pain without another complication reported improvement in pain less frequently (48% vs. 72%) and worsening pain more frequently (37% vs. 6%). Existing SUI worsened in 65% of women and 75% developed new SUI. There appears to be discordance between reporting global improvement with worsening of commonly measured clinical outcomes. Conclusion: Outcome data are important for counseling women about the risks and benefits of TETOT. Women and clinicians may have different attitudes to the possible benefits of TETOT, as evidenced by women reporting feeling better despite continuing pain or SUI. Conventional outcome measures do not adequately capture all outcomes that are important to patients.